A rare case of intracranial solitary fibrous tumor that is still alive after multiple surgical resections: a case report and review of the literature - Gao, YiMeng; Xu, Yan; Xie, RuiZhi; Shen, YouBi; Xue, DaoJin; Zhen, Zheng; Lu, JingJing; Huang, Tao; Peng, ZiZhuang (Frontiers in Neurology, 2023)
A Solitary Fibrous Tumor (SFT) is a rare, aggressive, and metastasis- and recurrence- prone mesenchymal tumor. In this case report and review, we describe a rare instance of intracranial SFT, discovered for the first time. It was discovered in 2008 and following total surgical removal, the pathology was categorized as hemangiopericytoma cell tumor (HPC) at the time by WHO tumor criteria. An imaging review 8 months after surgery revealed a tumor recurrence: combined radiation and gamma-knife therapy was continued throughout this time. The tumor did not metastasis until June 2018 when it presented in the pancreas with ruptured bleeding and a postoperative pathology was suggestive of SFT. Fortunately, the patient is still alive nearly 3 years after the 2020 surgery, after staged surgical resection and combined multimedia therapy, with no imaging or clinical evidence of a recurrent intracranial primary lesions. To our knowledge, there is no previous record of using a combined treatment modality for Intracranial Solitary Fibrous Tumor (ISFT). Combined with an account of the patient's experience, we empirically describe a combined approach with a preference for gross-total resection (GTR), supplemented by multimodal assistance with stereotactic (radiotherapy), gamma knife (GK), molecular targeting, and immunization for patients admitted acutely, with accurate preoperative identification and aggressive management after intraoperative case response to maximize treatment of recurrent ISFT and improve prognosis. We recommend multimodal management for SFT with prolonged-term recurrence and metastases, both for the control benefits of GTR, RT, or GK for local recurrence and for the positive prognosis of targeted and immune metastases.